TOURISM AND INFORMALITY: AN ANALYSIS OF INDIVIDUAL EVENTS ON THE NORTH COAST OF RIO GRANDE DO SUL - Kruel, Alexandra Jochims (Universidade de Santa Cruz do Sul, 2018)
This article comes from the reflection on texts by Ignacy Sachs, an expert of development, that addresses important contemporary issues to society, in a combination of the themes: economic growth, social equity and environmental preservation. Among the themes, there is the question of eradicating poverty and social exclusion, through decent job. The author argues that the inclusion by the job combines economic and social objectives, and that exercising the right of working, promotes self-esteem, opportunities for self-fulfillment and advancement in the social scale. On the other hand, he denounces the poor distribution of workload socially necessary and a worldwide epidemic of jobless growth, and he argues that in Brazil, especially, most of the work is in small enterprises, many of those where people work in conditions of precariousness and informality. In this sense, the author points to a striking reality in the country and he asks: Who can say how it works in Brazil, the so-called informal economy, how many workers do participate in it and how does it happen? Because of those questions, this article was written, a brief attempt to demonstrate some of the ways the informal economy operates in Brazil, in a context marked by seasonality: tourism, in a which huge number of people move to different places searching for home, leisure, employment opportunities and income, formalized or not. It is perceived in this article, informal economic activity as a survival practice. The study was conducted in the ethnography method, in a medium-size city of the North Coast of Rio Grande do Sul during the summer season of 2009 and 2010. The article starts with a contextual approach, which it comes to tourism, essentially. Following, it is presented a section on informality and practical entrepreneurial survival and searching for better living conditions. The third section relates to the methodological design, followed by ‘findings’ of the research and, finally, the final thoughts.